Health care utilization and outcomes in older adults after Traumatic Brain Injury: A CENTER-TBI study. Issue 8 (August 2022) - van der Vlegel, Marjolein; Mikolić, Ana; Lee Hee, Quentin; Kaplan, Z.L. Rana; Retel Helmrich, Isabel R.A.; van Veen, Ernest; Andelic, Nada; Steinbuechel, Nicole v.; Plass, Anne Marie; Zeldovich, Marina; Wilson, Lindsay; Maas, Andrew I.R.; et al.
Highlights: In the CENTER-TBI study about a half of older adults(≥65) were admitted to the intensive care unit. Lower educational level and pre-injury conditions are important predictors of poorer outcomes across different domains. Increased age is associated with poorer global functioning and physical HRQoL, but not with mental health outcomes. Older adults have a high mortality rate, however, there should not be pessimism about outcomes in older adults who survive. Abstract: Introduction: The incidence of Traumatic Brain Injury (TBI) is increasingly common in older adults aged ≥65 years, forming a growing public health problem. However, older adults are underrepresented in TBI research. Therefore, we aimed to provide an overview of health-care utilization, and of six-month outcomes after TBI and their determinants in older adults who sustained a TBI. Methods: We used data from the prospective multi-center Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI) study. In-hospital and post-hospital health care utilization and outcomes were described for patients aged ≥65 years. Ordinal and linear regression analyses were performed to identify determinants of the Glasgow Outcome Scale Extended (GOSE), health-related quality of life (HRQoL), and mental health symptoms six-months post-injury. Results: Of 1254 older patients, 45% were admitted to an ICU with a mean length of stay of 9 days. Nearly 30% of the patients received inpatient rehabilitation. In total, 554/1254 older patients completed the six-month follow-up questionnaires. The mortality rate was 9% after mild and 60% after moderate/severe TBI, and full recovery based on GOSE was reported for 44% of patients after mild and 6% after moderate/severe TBI. Higher age and increased injury severity were primarily associated with functional impairment, while pre-injury systemic disease, psychiatric conditions and lower educational level were associated with functional impairment, lower generic and disease-specific HRQoL and mental health symptoms. Conclusion: The rate of impairment and disability following TBI in older adults is substantial, and poorer outcomes across domains are associated with worse preinjury health. Nonetheless, a considerable number of patients fully or partially returns to their preinjury functioning. There should not be pessimism about outcomes in older adults who survive.